2021
DOI: 10.1097/ana.0000000000000769
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed Fluid Therapy Versus Conventional Fluid Therapy During Craniotomy and Clipping of Cerebral Aneurysm: A Prospective Randomized Controlled Trial

Abstract: Background: Fluid imbalance is common after aneurysmal subarachnoid hemorrhage and negatively impacts clinical outcomes. We compared intraoperative goal-directed fluid therapy (GDFT) using left ventricular outflow tract velocity time integral (LVOT-VTI) measured by transesophageal echocardiography with central venous pressure (CVP)-guided fluid therapy during aneurysm clipping in aneurysmal subarachnoid hemorrhage patients.Methods: Fifty adults scheduled for urgent craniotomy for aneurysm clipping were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…6 Literature on GDFT in the neurosurgical population is limited with contradictory results. [11][12][13][23][24][25] Akin to our study, estimation of fluids by GDFT has led to a lesser intraoperative fluid requirement than conventional CVP-guided regimen in studies on renal transplant recipients. [26][27][28] De Cassai et al used PPV to guide fluid management to achieve adequate urine output and found it to be as effective as liberal fluid therapy.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…6 Literature on GDFT in the neurosurgical population is limited with contradictory results. [11][12][13][23][24][25] Akin to our study, estimation of fluids by GDFT has led to a lesser intraoperative fluid requirement than conventional CVP-guided regimen in studies on renal transplant recipients. [26][27][28] De Cassai et al used PPV to guide fluid management to achieve adequate urine output and found it to be as effective as liberal fluid therapy.…”
Section: Discussionmentioning
confidence: 67%
“… 6 Literature on GDFT in the neurosurgical population is limited with contradictory results. 11 12 13 23 24 25 …”
Section: Discussionmentioning
confidence: 99%
“…A previous study among aneurysmal subarachnoid hemorrhage patients by Bloria et al 27 also reported that the implementation of goal-directed fluid therapy could reduce intraoperative fluid intake. Results of this study failed to show a reduction in the ICU length of stay and postoperative complication rates.…”
Section: Discussionmentioning
confidence: 93%
“…Trails have shown a benefit of goal-directed fluid therapy on postoperative outcomes in neurosurgical patients. 39 The definition and assessment of organ dysfunction have varied between studies, leading us to adopt the SOFA score, a more pragmatic and widely accepted definition.…”
Section: Future Research Opportunitiesmentioning
confidence: 99%